(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2014)
The purpose of the present research adresses the composition of a musical work using computing automation mechanisms, along with indigenous melodies as thematic material. Compositional process is based on the selection of a melody, its unfolding on heights and durations, and its translation to numerical notation. Heights are treated by Pitch Class Sets theory and arithmetical basic operations are applied to durations. Immediately afterwards, musical structures are elaborated and later they became formalized. A composer assistance software was used (PWGL) to carry out this work and computing environment of graphical programming aimed at objects based on the Common Lisp language.